2 - Teacher Education, Common Purpose and the Forging of Multiple Publics in South Africa - Hoffmann, Nimi; De Kock, Tarryn; McDonald, Zahraa; Sayed, Yusuf (Africa Development, 2020)
In an important scholarly intervention on African publics, Raufu Mustapha argues that the multiplicity of publics is not an obstacle but instead a creative resource that can be used to forge common purpose through public deliberation. However, he does not elaborate how common purpose operates and to what effect. In this article, we examine the dynamics of common purpose among student teachers in South Africa. Teachers inculcate the dispositions and habits of public deliberation in young people. How teachers are trained and where they teach is therefore crucial to understanding the constitution of publics. We analyse data from a cohort of student teachers regarding their reasons for becoming teachers, their future plans and their anxieties about their profession. We find little evidence of race and class differences among student teachers. Instead, the evidence suggests that student teachers shared a common purpose informed by hyper-particularistic notions of the public, which was not only raced and classed, but also limited to a narrow understanding of their own community. In light of this, we seek to explain how policy contributes to the conditions under which common purpose leads to segregated publics, closing off the generative possibilities of multiple publics.